Analysis of Financial Stability Factors, Financial Targets, External Pressure, Inefficient Monitoring and Rationalization of the Financial Statements Fraud - Dewi Khornida Marheni; Suryati Suryati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Financial statements are a medium to provide useful information for stakeholders and parties involved. Correct information will help all parties to make the right decisions in carrying out economic or business activities. Fraud is common in the financial and non-financial industries today. Fraud in the financial industry is commonly referred to as financial statement fraud. Up to the third quarter of 2018, 36 banks indicated the occurrence of fraud. This study aims to examine the fraud triangle factor in detecting financial statement fraud. The object of this study uses 43 banking companies listed on the Indonesia Stock Exchange period 2015-2019. Analysis data was using panel regression analysis. The results show there is a significant relationship between financial stability and the rationalization of financial statement fraud. Meanwhile, financial targets, external pressure, and ineffective monitoring did not have a significant effect on financial statement fraud.